Immobilized molybdovanadophosphoric acids on SBA-15 for selective oxidation of alkenes - Raj, N. K. K.; Deshpande, S. S.; Ingle, Rohit H.; Raja, T.; Manikandan, Palanichamy (4th International Symposium on Nanoporous Materials, 2005)
Vanadium substituted molybdophosphoric acids have been immobilized on amine functionalized SBA-15 and characterized by different techniques. Small angle X-ray scattering analysis and SEM technique provide evidence for the structural integrity of the samples. UV-Vis, NMR and IR data confirm the incorporation of molybdovanadophosphoric acids onto the amine functionalized SBA-15. The textural properties of these materials were studied by nitrogen sorption studies. Oxidation of cyclooctene and norbornene was carried out with oxidants in aqueous (aq. H2O2) and non-aqueous (TBHP extracted in dichloroethane) medium. The reactions were carried out with both the neat catalysts (homogeneous) and the immobilized catalysts (heterogenized) and the results were compared. The selectivity of the desired products was always > 99% with the immobilized catalyst with both aq.H2O2 and TBHP. However, while the leaching was negligible in the non-aqueous medium, the aqueous medium leads to considerable leaching. The immobilized catalysts could be separated after the reaction and the reusability of the catalyst has also been demonstrated especially with oxidant in the nonaqueous medium.

Microwave promoted solvent-free one-pot synthesis of N,N `-disubstituted urea derivatives - Jadhav, Vinod H.; Deshpande, S. S.; Borate, Hanumant B.; Wakharkar, R. D. (Journal of Chemical Research-S, 2005)
An efficient one-pot synthesis of N,N -disubstituted urea derivatives from substituted anilines, ethyl chloroformate and methyl anthranilate or methyl 3-amino-2-butenoate under microwave irradiation is reported.
Keywords: Anilines; methyl 3-amino-2-butenoate; methyl anthranilate; Microwave; urea derivatives